2017
DOI: 10.1016/j.hpb.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery pathway in patients undergoing distal pancreatectomy: a case-matched study

Abstract: An ER pathway for DP yielded an earlier postoperative recovery and shortened LOS in uneventful patients. Postoperative morbidity and readmissions were similar in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The characteristics of the 19 included articles, which comprised 7 cohort studies (8, 2328) and 12 case-control studies (7, 2939), are shown in Table 1, which totally contains 3387 patients. Thirteen studies (8, 23, 26, 2834, 3739) included patients undergoing PD, one study (35) included patients undergoing distal pancreatectomy (DP), one study (25) included patients undergoing proximal pancreatic resection, one study (36) included patients undergoing laparoscopic pancreatoduodenectomy (LDP), and three studies (7, 24, 27) included patients undergoing two forms of pancreatectomy.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 19 included articles, which comprised 7 cohort studies (8, 2328) and 12 case-control studies (7, 2939), are shown in Table 1, which totally contains 3387 patients. Thirteen studies (8, 23, 26, 2834, 3739) included patients undergoing PD, one study (35) included patients undergoing distal pancreatectomy (DP), one study (25) included patients undergoing proximal pancreatic resection, one study (36) included patients undergoing laparoscopic pancreatoduodenectomy (LDP), and three studies (7, 24, 27) included patients undergoing two forms of pancreatectomy.…”
Section: Resultsmentioning
confidence: 99%
“…However, rates of pancreatic fistulae and readmissions were similar compared to non‐ERAS pathway patients 7 . Similarly, Pecorelli et al 5 found ERAS pathway patients to be associated with earlier recovery of gastrointestinal function and shorter length of stay, but postoperative morbidity remained similar between ERAS and non‐ERAS groups.…”
Section: Discussionmentioning
confidence: 86%
“…While an inherent objective of implementing perioperative pathways is reducing variation in care, adherence to pathways is arguably an equally valuable aspect in optimizing patient care. In fact, Pecorelli et al 5 reported that adherence to items in their ERAS pathway ranged from 15% to 100%. An assessment of colorectal ERAS pathway adherence among 12 hospitals in four European countries revealed that adherence to pathway interventions ranged from 6% to 95% 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vollmer et al proposed that improved process management can mitigate the impact of preoperative risk and effectively deliver quality advances, despite traditional outcomes that may already meet or exceed benchmark outcomes for a given major surgical procedure . Implementation of a clinical pathway as a tool for introducing a well‐established process of care has been reported to be associated favorably with short‐term outcomes after DP, including length of hospital stay in single institutional studies …”
Section: Discussionmentioning
confidence: 99%